High‐Temperature Creep Behavior of SiOC Glass‐Ceramics: Influence of Network Carbon Versus Segregated Carbon. Issue 12 (5th September 2014) - Ionescu, Emanuel; Balan, Corneliu; Kleebe, Hans‐Joachim; Müller, Mathis M.; Guillon, Olivier; Schliephake, Daniel; Heilmaier, Martin; Riedel, Ralf
Abstract : Three silicon oxycarbide samples with different carbon contents are analyzed in the present study with respect to their high‐temperature creep behavior. The tests were performed in compression at 1100°C, 1200°C, and 1300°C; in this temperature range the mechanism of creep relies on viscoelastic flow within the samples and has been modeled with the Jeffreys viscoelastic model. After the release of the applied mechanical stress, a viscoelastic recovery behavior was observed in all samples. The creep behavior of the investigated samples indicates two rheological contributions in SiOC: (i) a high viscous answer, coming from the silica‐rich network, and (ii) an elastic response from the segregated carbon phase within the samples. Furthermore, two distinct effects of the carbon phase on the HT creep behavior of SiOC were identified and are discussed in the present paper: the effect of the carbon presence within the SiOC network (the "carbidic" carbon), which induces a significant increase in the viscosity and a strong decrease in the activation energy for creep, as compared to vitreous silica; and the influence of the segregated carbon phase (the "free" carbon), which has been shown to affect the viscosity and the activation energy of creep and dominates the creep behavior in phase‐separated silicon oxycarbides.